Contrasting patterns of the extreme drought episodes of 2005, 2010 and 2015 in the Amazon Basin - Panisset, Jéssica S.; Libonati, Renata; Gouveia, Célia Marina P.; Machado‐Silva, Fausto; França, Daniela A.; França, José Ricardo A.; Peres, Leonardo F. (International journal of climatology, 2018)
Spatial patterns of standardized anomalies of precipitation (P ‐ upper panels), LST (L ‐ middle panels) and solar radiation (R ‐ lower panels) relative to 2000–2015, during 2005 (JJAS ‐ left panels), 2010 (JJAS ‐ central panels) and 2015 (ONDJ ‐ right panels). Record‐breaking of minimum precipitation and maximum LST and solar radiation values for the 15‐year period are demarked by contour lines. Future climate scenarios point to an increase in the frequency of extreme droughts events, even in humid biomes. Throughout the 21st century, large areas of the Amazon basin experienced the most severe droughts ever recorded with special emphasis on the 2005 and 2010 events due to their severity and extent. Currently, there is an increased demand to understand the geographic extent and seasonal variability of climate variables during drought events, especially with respect to the social and environmental impacts. In this study, we aim to compare the observed climate conditions during the drought episodes of 2005, 2010 and 2015. We perform a detailed assessment of the measured precipitation, land‐surface temperature (LST) and solar radiation anomalies. We provide evidence that the anomalous precipitation deficit during 2015 exceeded the amplitude and spatial extent of the previous events, affecting more than 80% of Amazon basin, particularly the eastern portion. The pronounced lack of rainfall availability during late spring and early summer, coincident with radiation and temperature surpluses during these years are significant and notable. Changed meteorological spatial patterns were observed, with precipitation and radiation being the most prominent parameters in 2005, whereas precipitation and LST were most relevant in 2010. Understanding the behaviour and interactions of pertinent meteorological variables, as well as identifying similar or divergent patterns over the region during distinct extreme events, is essential for the improvement of our knowledge of Amazon forest vulnerability to climate fluctuation changes.